Faktor Ibu yang Memengaruhi Stunting Baduta di Kawasan Timur Indonesia Tahun 2018 - Ilham Aminu Rosyid; Titik Harsanti (Politeknik Statistika STIS, 2022)
Stunting is the main malnutrition in Indonesia. One of the factors that affect stunting is maternal factor. Mothers play an important role in the process of children growth and development so that mothers are very important in overcoming malnutrition in children. The purpose of this study was to determine the maternal factor that influenced stunting the baduta in Kawasan Timur Indonesia (KTI) 2018. This study used Riskesdas 2018 data and analysis unit for baduta in KTI. The variables used are maternal education, mother's work status, classification of residence, consumption of tablet tambah darah, antenatal-care (ANC) visits, and consumption of mother alcoholic drinks. Data analysis uses descriptive analysis and binary logistics regression. The results of the analysis showed that there were 29.5 percent of baduta stunting in KTI. Mother's education, residential classification, and visit (ANC) have a significant effect on baduta stunting in KTI. Baduta stunting tendencies are greater in baduta with mothers with less educated mothers (OR=1,225), living in rural areas (OR=1,165), and ANC visits are less than 4 times (OR=1,12).